'Translations around us' – the amount of translated text in everyday life. - Leena Salmi (Finland, 2022)
The paper reports on the follow-up of a diary study measuring the proportion of translations read daily (Paloposki 2006, Vihonen & Salmi 2007). Data was collected in the years 2007 to 2010 using a text diary where respondents filled in (electronically or on paper) all texts they read during one single day. They were also asked to specify whether the texts read were translations or not. The diary also contained a column for comments in case there were, for instance, doubts on the nature and origin of the text. The data currently comprises text diaries from 93 translator students and 30 non-students. The results from this group of respondents show that the average time spent daily using different kinds of texts is 5 hours 19 minutes for the students and 5 h 54 min for the non-students. Based on this study, it seems that the proportion of translations in our daily reading is approximately one third (33% for the students, 39% for the non-students). The study also tells us about reading habits: the students, for example, used less time reading newspapers and than the group of non-students.